2015
DOI: 10.2474/trol.10.35
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Transmission Characteristics during Soft-Start of Hydro-Viscous Drive Considering Fluid-Inertia Item

Abstract: Considering the influence of the fluid-inertia item on dynamic transmission characteristics during soft-start of hydro-viscous drive (HVD), theoretical models were derived with the aim of revealing the effect of engagement pressure, lubricant viscosity, viscosity-temperature characteristics, surface roughness and the ratio of inner and outer radius of plates on total torque and viscous torque. The results indicate that the increase of engagement pressure and lubricant viscosity shortens soft-start time and inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Because there are double arc oil grooves on the surface of the friction disc, the effective area coefficient ψ is defined as the ratio of the area of nonoil grooves to the total area, and the contact area ratio B is fully taken into account. en, the braking torque between friction pairs during soft start-up is as follows [11]:…”
Section: Hvd Torquementioning
confidence: 99%
See 1 more Smart Citation
“…Because there are double arc oil grooves on the surface of the friction disc, the effective area coefficient ψ is defined as the ratio of the area of nonoil grooves to the total area, and the contact area ratio B is fully taken into account. en, the braking torque between friction pairs during soft start-up is as follows [11]:…”
Section: Hvd Torquementioning
confidence: 99%
“…Chen et al obtained that the nonlinearity of the pressure performance curve is one key cause of the poor start-up smoothness [10]. Cui et al studied the influence of the fluid-inertia item on the HVD dynamic transmission [11]. e Isight integrated optimization design platform of friction pairs in HVD was built, and the groove structure parameters were optimized [12].…”
Section: Introductionmentioning
confidence: 99%
“…The experimental results showed that both the data from experimental kinematic viscosities and computed dynamic viscosities of 8# hydrodynamic transmission oil were larger than that of 32# hydrodynamic transmission oil. Then 8# hydrodynamic transmission oil is more suitable for applications and popularize of HVD [21]. The fitting curve of viscosity versus temperature based on experimental viscosities as listed in Table 1 is shown in Fig.…”
Section: Viscosity-temperature Relationmentioning
confidence: 99%
“…Considering the surface roughness of the disks, Xie et al (2018) and Cui et al (2018) studied the dynamic characteristics of HVD during the soft-start process and obtained the pressure distribution of oil film and dynamic torque behavior using computational fluid dynamics methods. Based on the average flow model and G-T model, Jang et al (2011) and Cui et al (2015) performed simulations of wet clutch engagement or HVD including the drive torque and analyzed the influences of different parameters on the transmission torque. Iqbal et al (2015) developed an SAE#2 test setup mathematical model to analyze the dynamic behavior of the clutch at different phases of fluid lubrication during engagement cycle, so as to improve the performance and lifetime of clutches through testing and simulation.…”
Section: Introductionmentioning
confidence: 99%